30 Expression of AQP 1, 3, 5, and 9. (7th December 2018) - Zhu, C; Jiang, Z; Bazer, F; Johnson, G; Burghardt, R; Wu, G
Abstract: This study was conducted to determine the localization and expression of aquaporins (AQPs) 1, 3, 5, and 9 in the porcine placenta and uterus during estrous cycle and gestation. In Exp. 1, uterine endometrium samples were collected from crossbred gilts at different stages of estrous cycle (days 11, 13, 15, and 17) and gestation (days 11, 13, 15, and 17). Placental samples were collected on days 25 and 60 of gestation. In Exp. 2, an established porcine trophectoderm cell line (pTr2) was used to study effects of reproductive hormones [estrogen (E2), progesterone (P4), and relaxin] on AQP expression. The results showed that AQP 1, 3, 5, and 9 were mainly expressed in the luminal epithelium and glandular epithelium of endometrium, with some being distributed in blood vessels of the endometrial stroma. The protein expression of AQP 1, 3, 5, and 9 in the endometrium changed dramatically during different stages of the estrous cycle (P < 0.05). The AQP 1, 3, 5, and 9 proteins were mainly expressed in the allantoic-chorion, amnion, and microvessels of the placenta. Compared to the control group, 0.025–0.1 ng E2/mL increased (P < 0.05) the AQP3 protein abundance, while 20 ng P4/mL increased (P < 0.05) the abundances of AQP 3, 5 and 9 proteins in pTr2 cells. Likewise, 25–50 ng relaxin/mL increased (P < 0.05) the protein abundances of AQP1 and AQP3 in pTr2 cells. Collectively, these results indicate that AQP 1, 3, 5, and 9 may play an important role in regulating water transport and homeostasis in the reproductive system of gilts during the estrous cycle and gestation. Supported by USDA-NIFA and NSFC. *Correspondence: g-wu@exchange.tamu.edu Key Words: